Respiratory microbiota imbalance in children with Mycoplasma pneumoniae pneumonia - Wang, Yacui; Yu, Xiaoran; Liu, Fang; Tian, Xue; Quan, Shuting; Jiao, Anxia; Yang, Xuemei; Zeng, Xi; Jiao, Weiwei; Qi, Hui; Xu, Fang; Li, Qinjing; et al. (Emerging microbes & infections, 2023)
Although previous studies have reported the dysregulation of respiratory tract microbiota in infectious diseases, insufficient data exist regarding respiratory microbiota imbalances in the lower respiratory tracts (LRTs) of children with Mycoplasma pneumoniae pneumonia (MPP). Here, we analysed the microbial community using 16S rRNA gene sequencing. Finally, bronchoalveolar lavage fluid (BALF) samples from 158 children with MPP and 29 with bacterial or viral pneumonia (control group) were collected. The diversity of the microbial community was significantly different between the two groups. A significantly increased abundance of Tenericutes and Mycoplasma was detected in the MPP group, exceeding 67% and 65% of the total bacterial population, respectively. Using Mycoplasma abundance as the diagnostic method, the sensitivity and specificity of the model was 97.5% and 96.6%, respectively. Compared to the mild MPP group, lower alpha diversity and significantly increased Mycoplasma abundance were found in the severe MPP group (P < 0.01). The abundance of Mycoplasma was positively correlated with complications and clinical indices in children with severe MPP compared with children with mild MPP. Our study describes the features of the LRT microbiota of children with MPP and uncovered its association with disease severity. This finding may offer insights into the pathogenesis of MPP in children.